Generating of reformat slices in neural and cardio‐tomography - Mockus, Laimonas; Meilūnas, Mečislavas; Paulinas, Mantas; Ušinskas, Andrius; Zakarkaitė, Diana (Mathematical Modelling and Analysis, 2007)
A lot of medical diagnostics problems are related to the reconstruction of three dimension (3D) images from the cross sections of the regions of interest. Such reconstructions are very desirable for evaluation of disease or planning of surgical treatment. This paper reviews recent 3D preprocessing work of authors in human brain blood vessels structure recognition and localization of aneurysms as well as analysis of the right ventricular of the human heart. Here we present some approximation techniques for generation of reformatted images. First Published Online: 14 Oct 2010